Recent Trends in the Study of Music of the Fourteenth, Fifteenth, and Sixteenth Centuries - Leach, E; Fallows, D; Van Orden, K (University of Chicago Press, 2015)
Leonardo da Vinci famously characterized music as “giving shape … to invisible things”;1 the authors of these three essays on recent trends in the study of music illuminate a range of scholarly strategies that interpret and render meaningful the fleeting sounds of music. Two of the essays, by Elizabeth Eva Leach and Kate van Orden, trace some ramifications of the cultural turn in music research. As in other humanistic disciplines, musicologists are opening new lines of inquiry that apply approaches from gender theory and psychoanalysis. As well, they pose questions about the status of the composed work versus musical improvisation, and other inquiries focus on popular repertories and music of the New World. David Fallows draws attention to the impact that performers and their choice of repertory have had on scholarly agendas, and takes into account the impact of recording technology. He further addresses evolving standards for critical editions, as does van Orden, who notes the particular advantages for music of a gradual move from fixed editions on paper to more dynamic virtual editions. All three authors note and assess the impact of technological developments on current research. Elizabeth Eva Leach, whose Guillaume de Machaut: Secretary, Poet, Musician received the 2012 Phyllis Goodhart Gordan Book Prize from the Renaissance Society of America, focuses her essay around four central issues in the study of fourteenth-century music. First, the incorporation of interdisciplinary approaches from history, literature, and the visual arts proves crucial in creating a richer understanding of musical life. A second approach pays fresh attention to the context of musical works within manuscripts, rather than extracting works for modern editions that arrange them by genre. The third area involves geography: a new awareness of the fluidity with which music and musicians crossed borders has opened new perspectives on the porous boundaries between French and Italian spheres of music making and on musical life in Eastern Europe. Finally, online resources allow scholars more ready access to work from other disciplines and across geographical boundaries. These approaches should encourage greater integration of music and its social functions in studies of history and culture of the fourteenth century. David Fallows is the author of foundational studies of central composers of the fifteenth century, and he is one of the preeminent scholars of fifteenth-century music.2 He surveys changing standards and ideals for the preparation of critical editions of music, as well as the impact of performers and the recording industry in shaping topics for research. As a scholar who has actively collaborated with performers on various recording projects over the past forty years, he offers well-informed insights about the advantages of active cooperation between performers and scholars. His essay outlines general trends in research and performance during the past several decades, but he refrains from providing specific citations. Kate van Orden’s Music, Discipline, and Arms in Early Modern France received the 2006 Lewis Lockwood Award from the American Musicological Society, and her most recent book is Music, Authorship, and the Book in the First Century of Print. While noting that archival and source studies continue as a vital component of musicological study for sixteenth-century music, she focuses on new developments in four areas of research: improvisation, histories of singers and singing, new approaches to the study of music in the New World, and the impact of digital technology on editing of music. She points to the reevaluation of established composers and written repertories in the light of new inquiries into oral practices, and she cites some recorded performances that put improvisation into practice. These new lines of inquiry challenge traditional hierarchies of scholarship on music and suggest more nuanced interactions between oral and written practices. Music’s “invisible things,” and the related issues and questions that they pose for scholars, continue to stimulate tangible and imaginative research in this lively field, as these essays abundantly demonstrate.